Information Literacy and Discourse Analysis for Verifying Information among EFL Learners - Yaseen Azi; Sami Abdullah Hamdi; Mohammed Okasha (Asociación Colombiana de Profesores de Ingles, 2024)
The task of verifying credible and original information is now more complicated, especially for undergraduate students. This study uses information literacy and discourse analysis to develop English as a foreign language learners' critical reading skills while verifying information on social media. A reading test including false news was used to assess the learners' awareness of the credibility of social media information. Then, they were divided into experimental and control groups. The experimental group was trained in evaluating a set of false news using information literacy and discourse analysis skills. The control group did not receive any training. The experiment was conducted again on both groups. The results show a significant improvement among the experimental group compared to the control group. The findings of this study shed light on the growing need for creating a pedagogical space in English as a foreign language classroom that focuses on raising learners' awareness of information literacy and discourse analysis skills to read with critical perspectives.